The application of Entropy-TOPSIS method in solving the time and attendance system software selection problem of a private hospital in Turkiye / Norazean Nordin, Eaisya Nurfarhana Samat and Fairuz Noraainaa Adam - Nordin, Norazean; Samat, Eaisya Nurfarhana; Adam, Fairuz Noraainaa (2024)
Automated time and attendance systems track employee attendance, calculate working days, overtime hours, late arrivals, and generate attendance reports, thereby improving workforce productivity. The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method was adopted to rank the alternatives. However, TOPSIS lacks a mechanism for weight elicitation. Thus, the integration of the Entropy method with TOPSIS was proposed to address the shortcoming. Hence, the goal of this study is to integrate the Entropy-TOPSIS method, select the most suitable time and attendance system software, and conduct sensitivity analysis to validate the ranking stability. Real-life data about time and attendance system software selection for hospital in Turkiye was used to integrate the Entropy-TOPSIS method.